β-lapachone exerts hypnotic effects via adenosine A1 receptor in mice - 이도현 (The Graduate School, Ajou University, 2024)
Sleep is one of the most essential physiological phenomena for maintaining health. Sleep disturbances, such as insomnia, are often accompanied by psychiatric or physical conditions such as impaired attention, anxiety, and stress. Medication used to treat insomnia have concerns about potential side effects with long-term use, so interest in the use of alternative medicine is increasing. In this study, we investigated the hypnotic effects of β-lapachone (β-Lap), a natural naphthoquinone compound, using pentobarbital-induced sleep test, immunohistochemistry, real-time PCR, and western blot in mice. Our results indicated that β-Lap exerts a significant hypnotic effect by showing a decrease in sleep onset latency and an increase in total sleep time in pentobarbital-induced sleep model. The results of c-Fos immunostaining showed that β-Lap decreased neuronal activity in the basal forebrain and lateral hypothalamus, which are wakefulness-promoting brain regions, while increasing in the ventrolateral preoptic nucleus, a sleep-promoting region; all these effects were significantly abolished by 8-cyclopentyl-1,3-dipropylxanthine (DPCPX), an adenosine A1 receptor (A1R) antagonist. Western blot analysis showed that β-Lap increased extracellular signal-regulated kinase phosphorylation and nuclear factor-kappa B translocation from the cytoplasm to the nucleus; these effects were inhibited by DPCPX. Additionally, β-Lap increased the mRNA levels of A1R. Taken together, these results suggest that β-Lap exerts hypnotic effects, potentially through A1R.
학위논문(석사)--약학과,2024. 8
Keywords: adenosine A1 receptor; hypnotic; insomnia; sleep; β-lapachone